Development of a bootstrap-model for determining the release of medicinal preparations in the human organism - Chorny, Alexandr; Savyak, Roman; Kondratov, Sergej (Eastern-European Journal of Enterprise Technologies, 2017)
We developed a bootstrap-model for evaluating the release kinetics of medicines in the organism and its computer realization. The model is based on the interpolation of experimental data for the release at pH 1.2; 4.5 and 6.8 by the linear and cubic splines and the use in the simulation of dissolution in the organism by passing the zones with the indicated pH values. The profile of the release is considered to be a random process, realized in separate points of time. In order to perform the bootstrap-simulation of a pseudo-profile of the release in the organism, we generated a spline-pseudo-profile of dissolution at pH 1.2 (imitation of stomach); by using it, we determined mass of the released preparation in 2 hours. Employing the data obtained, we built a spline-pseudo-profile of dissolution at pH 4.5 (duodenum), which matches a residual amount of the preparation. Next, in a similar way, we constructed a spline-pseudo-profile, corresponding to a residual quantity of the preparation, and determined the release at pH 6.8 (small intestine). The method devised is demonstrated on the example of the simulation of the release kinetics of the preparation Trizipin Long in the organism based on results of the release kinetics in vitro. The model makes it possible to estimate the mean profile, spread and confidence interval of the release. It is established according to results of the simulation that the release of the preparation Trizipin Long from a tablet of mass 1000 mg in the organism in 14 hours makes up on average 870 mg and, with a probability of 0.95, could be within the range from 788 to 946 mg. The advantage of the developed approach is its universality, as the method is not linked to any particular physical model of the dissolution and the release.